Angiotensin‐converting enzyme 2 in severe acute respiratory syndrome coronavirus and SARS‐CoV‐2: A double‐edged sword?. Issue 5 (19th April 2020) - Yan, Tiantian; Xiao, Rong; Lin, Guoan
Abstract: Human angiotensin‐converting enzyme 2 (ACE2) facilitates cellular entry of severe acute respiratory syndrome coronavirus (SARS‐CoV) and SARS‐CoV‐2 as their common receptor. During infection, ACE2‐expressing tissues become direct targets, resulting in serious pathological changes and progressive multiple organ failure or even death in severe cases. However, as an essential component of renin‐angiotensin system (RAS), ACE2 confers protective effects in physiological circumstance, including maintaining cardiovascular homeostasis, fluid, and electrolyte balance. The absence of protective role of ACE2 leads to dysregulated RAS and thus acute changes under multiple pathological scenarios including SARS. This potentially shared mechanism may also be the molecular explanation for pathogenesis driven by SARS‐CoV‐2. We reasonably speculate several potential directions of clinical management including host‐directed therapies aiming to restore dysregulated RAS caused by ACE2 deficiency. Enriched knowledge of ACE2 learned from SARS and COVID‐19 outbreaks can provide, despite their inherent tragedy, informative clues for emerging pandemic preparedness.